Best Answer

You cannot solve it though it is possible to evaluate the expression.

-5 + 9 * 6 = -5 + 54 = 49

Q: How do you solve negative 5 plus 9 times 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

It is: (-5-2) times -3 = +21

-3x + 5 = 20 -3x = 15 x = -5

It is 25/3 + 3y.

a negative times a positive is a negative so 2*-4=-8+10=2

-4 + -5 + -2 + -1 = -12 (negative 12).

Related questions

It is: (-5-2) times -3 = +21

25

-3x + 5 = 20 -3x = 15 x = -5

It is 25/3 + 3y.

To solve -2 plus 5 equals, it's probably easier to start with the positive number and add the negative number to it. The equation will look like this: 5 + (-2) = Because you are adding a negative number, you actually have to subtract the 2, rather than add it, so your answer will be 3.

a negative times a positive is a negative so 2*-4=-8+10=2

Twice. Between negative two and negative one.

Z= -1

-4 + -5 + -2 + -1 = -12 (negative 12).

-3 + -7 + 5 + -4 + -6 = -15

3*-5+27 equals 12.

4 + (-2) + 5 = 7 BECAUSE adding a negative number is the same as subtracting the number, so 4 + (-2) = 2 and 2 + 5 = 7